(E)-2-Bromobenzaldehyde oxime - Zonouzi, Afsaneh; Mirzazadeh, Roghieh; Ng, Seik Weng (International Union of Crystallography, 2011)
The configuration of the C=N double bond of the title compound, C 7H 6BrNO, is E; the non-H atoms are approximately coplanar (r.m.s. deviation = 0.038 Å). In the crystal, pairs of molecules are linked by a pair of O - H⋯N hydrogen bonds about a center of inversion, generating hydrogenbonded dimers.